Empowering EFL Learners’ Writing Performances through the Use of Peer Assessment - Wijaya, Kristian Florensio (Polyglot: Journal of Linguistics, Literature, and Language Education, 2025)
Feedback is one of the crucial elements that determine the quality of the teaching and learning process. In the EFL writing learning realm, second language educationalists need to be more conscientious and selective before capitalizing on specific feedback types appropriate for learners’ writing learning contexts. One of the rewarding types of feedback approaches worth further activation in second language writing learning dynamics is peer assessment. Previous researchers contended that peer assessment could potentially promote emotionally-supportive and positively-sound writing learning dynamics in which EFL learners begin cultivating robust motivation to practice their writing skills to the utmost development. This small-scale library study employed a thematic analysis to analyze the findings of 20 previously peer-reviewed scientific articles. With the support of a thematic analysis, the researcher is more likely to yield more precise, credible, and contextualized results since the reviewed findings are categorized into identical research themes. From the thematic analysis research results, peer assessment is proven to be an expedient pedagogical approach to be internalized at the onset of second language writing learning dynamics, as this strategy is a propelling force for strategic writing development, academic self-regulation, writing performance, confidence, and learner collaboration. From the above-depicted research outcomes, it is indispensable for educators to ascertain the meaningful use of peer assessment in order to promote fruitful writing learning outcomes in the presence of heterogeneous learners.